Dechlorophyllation of Cosmos caudatus Kunth., Morinda citrifolia, and Mangifera indica L. Leaves Methanolic Extract by Electrocoagulation Technique - Ratna Budhi Pebriana; Endang Lukitaningsih; Siti Mufidatul Khasanah (Faculty of Pharmacy, Universitas Gadjah Mada, 2017)
The present of chlorophyll is not expected in the isolation process of plant active constituent. Electrocoagulation is a potential dechlorophyllation method. This research aims to know the effectivity of electrocoagulation in the dechlorophyllation process of Cosmos caudatus Kunth., Morinda citrifolia, and Mangifera indica L. leaves methanolic extract as well as the effect to the total phenolic content. Electrocoagulation are performed using copper, silver, aluminum and iron plates as the electrode. Dechlorophyllation by extraction using n-hexane is performed as reference. The % absorbance of chlorophyll and % of total phenolic content of dechlorophyllated samples are measured spectrophotometrically. Electrocoagulation process reduces % absorbance of chlorophyll in Cosmos caudatus Kunth., Morinda citrifolia, and Mangifera indica L. leaves methanolic extract. The more the duration of electrocoagulaton process the lower the % absorbance of chlorophyll obtained. % absorbance of chlorophyll of the electrocoagulated extract according to paired t-test (P=0.95) are significantly different with the previous. One way ANOVA continued with LSD (P=0.95) shows that the % absorbance of chlorophyll from the electrocoagulated extract are significantly different with those extracted with n-hexane. Electrocoagulation process reduces total phenolic content along with duration of electrocoagulation.